2020
DOI: 10.1017/s0022215120001024
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of post-thyroidectomy hypocalcaemia: a systematic and narrative review

Abstract: AbstractObjectiveHypocalcaemia is the most common complication after total or completion thyroidectomy. This study assesses recent evidence on predictive factors for post-thyroidectomy hypocalcaemia in order to identify the patients affected and aid prevention.MethodTwo authors independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 62 publications
1
20
4
Order By: Relevance
“…Because postoperative calcium levels may be confounded by prophylactic calcium and calcitriol administration, or by low preoperative vitamin D levels, many groups preferred the measuring of intraoperative or postoperative intact PTH levels drawn at various time points in the early post-thyroidectomy period [ 10 , 14 , 20 ]. A recent statement on hypoparathyroidism of the American Thyroid Association found that the timing of PTH measurements in published studies has ranged from 10 min to 24 h post-thyroidectomy [ 14 ], and that a postoperative PTH level < 15 pg/mL is usually predictive of hypocalcemia [ 6 , 8 , 9 , 10 , 11 , 13 , 20 , 21 ]. However, serum PTH levels may remain stable within the first days after thyroidectomy and day 1 PTH levels may be accurate enough to predict hypocalcemia and direct the initiation of calcium supplementation [ 4 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because postoperative calcium levels may be confounded by prophylactic calcium and calcitriol administration, or by low preoperative vitamin D levels, many groups preferred the measuring of intraoperative or postoperative intact PTH levels drawn at various time points in the early post-thyroidectomy period [ 10 , 14 , 20 ]. A recent statement on hypoparathyroidism of the American Thyroid Association found that the timing of PTH measurements in published studies has ranged from 10 min to 24 h post-thyroidectomy [ 14 ], and that a postoperative PTH level < 15 pg/mL is usually predictive of hypocalcemia [ 6 , 8 , 9 , 10 , 11 , 13 , 20 , 21 ]. However, serum PTH levels may remain stable within the first days after thyroidectomy and day 1 PTH levels may be accurate enough to predict hypocalcemia and direct the initiation of calcium supplementation [ 4 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total thyroidectomy is one of the most frequently performed endocrine surgical procedures, and it can lead to serious complications, including temporary or permanent cordal palsy or postoperative bleeding, although hypoparathyroidism is the most frequent complication [ 4 , 5 , 6 ]. Hypoparathyroidism with hypocalcemia may affect 3–49% of patients undergoing thyroid surgery [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Many risk factors have been associated with an increased incidence of post-operative hypocalcemia.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations